The Healthcare Needs of Families Caring for Patients with Pulmonary Tuberculosis - Astuti Yuni Nursasi; Nadya Tiara Sabila; Muhamad Jauhar (Jurnal Keperawatan Indonesia, 2021)
Tuberculosis (TB) is a global public health problem. Families need to meet healthcare needs during the treatment of TB sufferers. This study aims to identify healthcare needs of families caring for patients with the disease. The cross-sectional study involved 83 families caring for TB patients. The research was conducted at a Primary Healthcare Center in an urban area in West Java. The results revealed that 60.2% of caregivers were 18–40 years old, 60.2% were female, 51.8% were senior high school educated, 43.4% were housewives, 86.7% had an income under the regional minimum wage, and 55.4% had cared for the TB patients for 3–6 months. The families had healthcare needs for emotional support (mean 33.72, SD 4.16); information support (mean 33.28, SD 4.09); instrumental support (mean 32.4, SD 3.73); and appraisal support (mean 28.01, SD 5.93). The greatest support need was how to encourage clients to take treatment completely (Score: 140); TB treatment information (Score: 138); financial support for chest x-ray costs (Score: 114); and how to assess patient behavior in maintaining health (score: 133). Based on the study result, the families need to improve their ability to give appraisal support during the patient's treatment. The identification of families’ healthcare needs in caring for patients with pulmonary TB can provide primary data for developing innovative programs integrated with DOTS programs in healthcare services to improve family support. Abstrak Kebutuhan Perawatan Kesehatan Keluarga yang Merawat Pasien Tuberkulosis. Tuberkulosis (TB) merupakan masalah kesehatan masyarakat global. Keluarga harus memenuhi kebutuhan perawatan kesehatan selama pengobatan pada pasien TB. Penelitian ini bertujuan untuk mengidentifikasi kebutuhan perawatan kesehatan pada keluarga yang merawat pasien TB. Penelitian cross-sectional ini melibatkan responden sebanyak 83 keluarga yang merawat pasien TB. Penelitian ini dilaksanakan di sebuah Puskesmas di Kota Depok, Jawa Barat. Penelitian ini melaporkan sebanyak 60,2% berusia 18–40 tahun, 60,2% perempuan, 51,8% lulus sekolah menengah atas, 43,4% ibu rumah tangga, 86,7% pendapatan di bawah upah minimum regional, 55,4% merawat pasien TB selama 3–6 bulan. Keluarga memiliki kebutuhan perawatan kesehatan untuk dukungan emosional (rerata 33,72, SD 4,16), dukungan informasi (rerata 33,28, SD 4,09), dukungan instrumental (rerata 32,4, SD3,73), dukungan penghargaan (rerata 28,01, SD 5,93). Kebutuhan tertinggi yaitu bagaimana mendorong pasien melakukan pengobatan secara tuntas (140), informasi pengobatan TB (138), dukungan keuangan untuk biaya pemeriksaan rontgen (114), dan bagaimana mengkaji perilaku pasien dalam mempertahankan kesehatan (133). Keluarga membutuhkan peningkatan kapasitas dalam memberikan dukungan penghargaan selama pengobatan pasien. Kebutuhan akan perawatan kesehatan pada keluarga yang merawat pasien TB dapat dijadikan data dasar dalam mengembangkan program inovatif terintegrasi dengan program DOTS di fasilitas layanan kesehatan dalam meningkatkan dukungan pada pasien TB. Kata kunci: keperawatan keluarga, sistem dukungan, Tuberkulosis paru